2016
DOI: 10.17221/68/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The practical use of computed tomography in evaluation of shell lesions in six loggerhead turtles (Caretta caretta)

Abstract: Six adult loggerhead turtles were found stranded and were rescued near Sicily within a period of 12 months. Macroscopically apparent lesions of the shell were present. After thorough physical examination, ketamine-dexmedetomidine-atipamezole induction and tracheal tube insertion all six patients underwent computed tomographic examination under inhalant anaesthesia with isoflurane. A vertebral lesion at the level of the 3 rd thoracic-lumbar vertebra with vertebral lamina and the vertebral body being involved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Therefore, precise knowledge of the anatomy of the sea turtle head is necessary to also contribute to the establishment of correct diagnoses. In order to obtain clinical images of the head, CT and magnetic resonance imaging have progressively gained credit for their ability to provide more data to assess the osseous and soft tissue structures of this region [ 3 , 4 , 7 , 33 , 46 , 47 ]. Diagnostics of several diseases involving the head of loggerhead sea turtles can be improved using CT imaging [ 7 , 33 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, precise knowledge of the anatomy of the sea turtle head is necessary to also contribute to the establishment of correct diagnoses. In order to obtain clinical images of the head, CT and magnetic resonance imaging have progressively gained credit for their ability to provide more data to assess the osseous and soft tissue structures of this region [ 3 , 4 , 7 , 33 , 46 , 47 ]. Diagnostics of several diseases involving the head of loggerhead sea turtles can be improved using CT imaging [ 7 , 33 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MPR sagittal images were obtained using bone and soft tissue kernels. The planimetric CT anatomy of the head allows a correct morphologic and clinical assessment of its anatomic structures in the loggerhead sea turtle [ 3 , 7 , 33 , 46 , 47 ]. The sagittal MPR kernel plane provided the best views of the midline structures of the head, whereas the transverse plane allowed us to better observe the anatomic relationships of the anatomic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Veterinarni Medicina, 65, 2020 (12): 511-527 https://doi.org/10.17221/50/2020-VETMED 2012; Spadola et al 2016a), as shown in a study reporting an intestinal mass in a green turtle (Figure 8) (Erlacher-Reid et al 2013).…”
Section: Reviewmentioning
confidence: 98%
“…Despite its high costs, the use of CT may reduce the treatment time, maximise the chances of successful rehabilitation, and consequently, reduce the cost associated with keeping the animal in captivity (Valente et al 2007a;Erlacher-Reid et al 2013;Spadola et al 2016a). Therefore, CT is a valuable non-invasive method for the clinical examination of sea turtles in the rehabilitation process (Spadola et al 2016a).…”
Section: Reviewmentioning
confidence: 99%
“…Studies using different methods of diagnostic imaging for diagnosis of organ function in chelonians have been published (Rubel and Kuoni 1991;DeShaw et al 1996;Hernandez-Divers and Hernandez-Divers 2001;Hernandez-Divers and Lafortune 2004;Wilkinson et al 2004;Silverman 2006;Gumpenberger 2011). Computed tomography (CT) is broadly applied as a diagnostic imag- ing method and is valuable in the characterisation of several diseases in chelonians (Gumpenberger and Henninger 2001;Gumpenberger 2002;Gumpenberger and Filip 2007;Marchiori et al 2015;Spadola et al 2016). The quantitative assessment of tissue density is expressed in Hounsfield units (HU, Kiefer and Pees 2011;Wyneken 2014;Marchiori et al 2015).…”
mentioning
confidence: 99%